Forced to go virtual. Working-from-home arrangements and their effect on team communication during COVID-19 lockdown. (August 2022) - Maurer, Marcel; Bach, Norbert; Oertel, Simon
Working-from-home arrangements have become increasingly important for firms' work organization. In this context, the COVID-19 pandemic has led to teams that previously did not work virtually being forced to interact and communicate virtually. In this study, we analyze changes in intra-team communication of four teams in a German medium-sized enterprise. Quantitative network analyses of email communication and qualitative analyses of interviews before and during the COVID-19 lockdown in spring 2020 show that flat hierarchies and self-managing processes helped team members to mitigate negative effects due to spatial and temporal dispersion in forced working-from-home arrangements. Moreover, analysis of the teams' communication networks shows that forced remote work can trigger faultlines to become salient but that team cohesion, identification with the team, and individuals taking on broker roles prevent negative effects of faultlines on team performance. In discussing these findings, our study contributes to the research on coordination and communication in virtual teams by analyzing contextual, organizational, team-related as well as individual factors that explain how and why teams differ in successfully implementing working-from-home arrangements.